2017
DOI: 10.1016/j.jgeb.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of some fermentation conditions for the production of extracellular amylases by using Chryseobacterium and Bacillus isolates from organic kitchen wastes

Abstract: Amylolytic bacterial isolates were obtained by starch-agar plate method from municipal solid wastes. Six amylolytic bacteria were isolated and the best two isolates, named as DY and W1, were selected based on clear zone ratio. The 16S rDNA sequence analysis identified DY and W1 isolates as Chryseobacterium sp. and Bacillus sp., respectively. Amylase production was optimized using basal media. The maximum level of amylase production was achieved from Chryseobacterium and Bacillus isolates after 60 h and 48 h of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 29 publications
2
41
0
1
Order By: Relevance
“…Similar observations were reported by Hasan et al (2017) too. The reduction in amylase activity after altering the pH of the culture medium might be due to the denaturation or inactivation of proteins.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar observations were reported by Hasan et al (2017) too. The reduction in amylase activity after altering the pH of the culture medium might be due to the denaturation or inactivation of proteins.…”
Section: Discussionsupporting
confidence: 91%
“…The availability of essential elements, coenzymes, nitrogenous constituents, and growth factors in yeast extract might be responsible for the amylase inducing property of the isolate. However, Hasan et al (2017) revealed peptone as the most stimulatory nitrogen source for maximum production of amylases from both Chryseobacterium sp. and Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations